A quantum perspective on oscillation frequencies in axion dark matter experiments - Jaeckel, Joerg; Montoya, Valentina; Quint, Cedric (Annalen der Physik, 2023)
In this paper, the time evolution of signals in axion dark matter experiments is considered from a quantum perspective. The aim is to illuminate the specific case of axion experiments and not to contribute new results to the general discussion of the quantum/classical connection. Classically, one expects a signal oscillating with a frequency equal to the axion mass whose amplitude is slowly rising due to the tiny interaction of the axions with ordinary matter. Quantum mechanically the latter time-scale arises from the small splitting in the energy levels induced by the interaction between the axions and the experiment. It is always present in suitable, sensitive experiments. Signals that oscillate with the axion mass arise from processes changing the axion number. For certain observables such oscillations are absent for special initial quantum states of the axions. Examples are shown where these special states can be affected by the experiment such that a signal oscillating with the axion mass re-appears. Suitable correlators that feature an oscillation with the axion mass are discussed, and comments on the connection to the classical treatment are provided. Explicitly, the Cosmic Axion Spin Precession Experiment (CASPEr) is studied, but these findings are expected to be adaptable to other axion dark matter searches.